2012
DOI: 10.1007/s10875-012-9678-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Peripheral γδT Cells Cytotoxicity Potential in Patients with HBV-Associated Acute-On-Chronic Liver Failure Might Contribute to the Disease Progression

Abstract: These results suggest that γδ T cells might participate in liver injury in HBV-ACLF patients by producing increased amounts of inflammatory cytokines and/or cytotoxicity ability. These findings provide novel information regarding the pathogenesis of HBV-ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
1
22
2
Order By: Relevance
“…Therefore, it is likely that effector memory Vd1 and Vd2 T cells may contribute to the immune control of HBV infection without causing liver pathology. The finding in the present study contrasts with the depletions of these cells in patients with HBV-associated liver disease and HBV-ACLF (10,11), which may facilitate liver damage. A role for Vd2 T cells in immunity against HCV was reported by Agrati et al (1), while the same group has provided evidence that Vd1 T cells contribute to liver damage in patients with HCV infection (2).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is likely that effector memory Vd1 and Vd2 T cells may contribute to the immune control of HBV infection without causing liver pathology. The finding in the present study contrasts with the depletions of these cells in patients with HBV-associated liver disease and HBV-ACLF (10,11), which may facilitate liver damage. A role for Vd2 T cells in immunity against HCV was reported by Agrati et al (1), while the same group has provided evidence that Vd1 T cells contribute to liver damage in patients with HCV infection (2).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Vd1 T cells, the most abundant cd T cell subset in the intestine, were expanded in the blood of patients with HBV-ACLF. cd from HBV-ACLF patients exhibited enhanced cytotoxicity and inflammatory cytokine production compared to their counterparts in chronic HBV patients and healthy controls, suggesting that cd T cells play a role in liver injury in HBV-ACLF (10).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…47,48 In this study, we found an increase in IL-17 producing cd T cells in HIV-infected patients, particularly in fast progressors. Our results suggest that IL-17 producing cd T cells may participate in HIV pathogenesis.…”
Section: Chronic Immune Activation Depletes Memory Vd 2 CD T Cells Insupporting
confidence: 50%
“…The major aetiologic agents of ACLF are alcohol and drugs in the West, whereas infectious etiologies predominate in the East [1]. In China, hepatitis B virus (HBV) infections account for 82% of all ACLF and the characteristic feature of ACLF is a acute deterioration in liver function over a short period and associated with a short-term mortality rate ranging from 50-90% [2,3]. Unfortunately, the exact mechanism of HBV-related ACLF is currently unclear.…”
Section: Introductionmentioning
confidence: 99%